2022
DOI: 10.23838/pfm.2021.00170
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging for lung cancer: a state-of-the-art review

Abstract: Lung cancer is the leading cause of cancer-related deaths worldwide, and imaging techniques such as chest radiography, computed tomography (CT), positron emission tomography (PET), and magnetic resonance imaging (MRI) play an important role in its diagnosis, staging, treatment planning, post-operative surveillance, and treatment response evaluation. Pulmonary MRI can non-invasively visualize structural and functional abnormalities in the lungs without using ionizing radiation, although it has been suggested th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 151 publications
0
14
0
Order By: Relevance
“…The current study shows that the depiction and morphologic evaluation of solid nodule in CODE and VIBE were not significant different from that in CT image. The depiction of part-solid nodules and purely ground-glass opacity nodules may be underestimated by MR [ 4 , 16 ], yet the number of part-solid nodules and purely ground-glass opacity nodules was too small to evaluate nodule detection and morphologic characterization in our study. In addition, it has been reported that UTE sequences could improve the detection rate of small nodules, especially for nodules larger than 4 mm, for which the detection rate was improved by more than 90% [ 2 , 16 , 25 ]; however, due to smooth the margins of nodule, the nodule dimensions were underestimated by about 1–2 mm [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The current study shows that the depiction and morphologic evaluation of solid nodule in CODE and VIBE were not significant different from that in CT image. The depiction of part-solid nodules and purely ground-glass opacity nodules may be underestimated by MR [ 4 , 16 ], yet the number of part-solid nodules and purely ground-glass opacity nodules was too small to evaluate nodule detection and morphologic characterization in our study. In addition, it has been reported that UTE sequences could improve the detection rate of small nodules, especially for nodules larger than 4 mm, for which the detection rate was improved by more than 90% [ 2 , 16 , 25 ]; however, due to smooth the margins of nodule, the nodule dimensions were underestimated by about 1–2 mm [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…While FID-based UTE sequences are commonly used to provide better visualization of endogenous lung parenchyma than conventional lung MRI sequences [ 4 ], a previous study has shown that the asymmetric echo-based CODE sequence was also sufficient to visualize lung structures in healthy subjects, despite slightly longer echo times than FID-based UTE sequences due to gradient-echo acquisition [ 11 ]. However, the feasibility of the CODE sequence in patients with various thoracic diseases has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MRI, with its superior soft tissue contrast, faces challenges in detecting smaller lesions, while PET-CT may yield a substantial rate of false positive results due to underlying inflammatory processes. Furthermore, there are challenges related to tumor heterogeneity, overdiagnosis, motion artifacts, radiation exposure, costs, accessibility, and the integration of multi-modal data [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…It is not possible using MRI to assess the airway and lung parenchyma, due to low proton density and artefacts due to respiratory and cardiac motion [ 48 ]. However, with recent advances related to MRI pulse sequences, post-processing software and analysis methods, multi-coil parallel imaging and acceleration methods, and the administration of contrast media, pulmonary MRI has become a considerable imaging modality in lung cancer [ 49 , 50 ]. On the one hand, higher lesion contrast can be expected at 3 T compared to 1.5 T machines [ 49 ].…”
Section: The Role Of Mri In Diagnosis and Follow-upmentioning
confidence: 99%